Profiling Vocational Students Sustainability Literacy in the Skills Domain of Food Waste Education - Nur Kamila Saldiana; Indriani Rachman; Anna Permanasari; Toru Matsumoto (Jurnal Pendidikan Sains Indonesia, 2025)
Food waste poses a serious environmental challenge that requires not only conceptual awareness but also practical sustainability competencies. This study aims to profile vocational high school students sustainability literacy in the skills domain of food waste education as a preliminary step toward developing interactive learning media. A total of 36 Grade X students in Bogor participated in a field trial using a prototype e-book entitled Awas Food Waste. Students were assigned to solve a contextual case, design digital posters, and present their solutions in class. Poster texts (365 words) were analyzed through word-frequency techniques, while oral presentations were assessed using a rubric adapted from Murray and Cotgrave. Results showed that frequently used terms indicated both problem recognition (e.g., sisamakanan [food leftovers], food waste, sampah [waste]) and proposed solutions (e.g., kompos [compost], maggot, organik [organic]). The presentation scores averaged 3.53 (median = 3; mode = 3), categorized as sufficientgood, with 22.2% of students achieving a very good level. These findings reveal that students are able to identify and communicate practical strategies to reduce food waste, although the depth and innovation of solutions remain limited. The study highlights a gap between awareness and applied action, underscoring the importance of scaffolding through interactive e-books and other digital media. This preliminary evidence serves as a baseline for designing pedagogically grounded interventions to strengthen vocational students sustainability skills and foster responsible environmental behavior